The Role Of Teachers' Pedagogical Competence In Improving Student Learning Outcomes At MA Muhammadiyah Balassuka-Tombolopao Sub-District-Gowa District-South Sulawesi - Muliana; Romelah; Dina Mardiana (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The research reviews the role of jurisprudence teachers' pedagogical competence in improving student learning outcomes at MA Muhammadiyah Balassuka, Kunciopao District, South Sulawesi, with the aim of the research being to determine the role of teachers' pedagogical competence and understanding what student learning outcomes are when teachers apply pedagogical competence in teaching at Madrasas. This research method is a qualitative approach, a case study type. Data collection was carried out through observation, interviews and documentation techniques. Meanwhile, data analysis uses the Spradley model. The teacher shows good mastery of the lesson material, as seen from the explanations that are coherent and easy for students to understand, so that they can produce good learning outcomes. Based on the application of jurisprudence teachers' pedagogical competencies, it is clear that by mastering the characteristics of students, teachers can plan and implement learning using learning strategies, learning methods and learning materials that are appropriate and appropriate for students. By mastering the characteristics of students, teachers can organize a learning process that helps various aspects of student development, including psychomotor aspects, affective aspects, creative aspects, emotional aspects, independence aspects and moral aspects.